Ideology, Politics and Axiology: Three Ways and Assumptions to Think about Educational Progress in Mozambique (Global Journal of Human-Social Science, 2024)
This reflection aims to be a simple contribution, in the most significant way possible, to the debate on the ways and assumptions to think about educational progress in Mozambique. It is, therefore, a reflection that, starting from an ideological discourse, and being based on the political perspective, flows into axiological reflection, that is, on the values that, according to Castiano and Ngoenha, are configured as being maximum exponents of education in the Mozambican conjuncture. The idea of educational progress, from a generic point of view, is also scrutinized by several Mozambican thinkers. However, the reading and interpretation given by the thought of the Mozambican philosophers Castiano and Ngoenha finds its possibility of application in the current Mozambican scenario, characterized, to a large extent, by instability and educational crisis.
Keywords: education; ideology; politics; axiology; progress